2001
DOI: 10.1136/vr.149.18.552
|View full text |Cite
|
Sign up to set email alerts
|

Infection of dogs in north‐west Spain with a Babesia microti‐like agent

Abstract: During 1996 a small, ring-shaped, piroplasm was observed in blood smears from 157 dogs in north-west Spain. None of them had previously been in areas endemic for Babesia gibsoni, which was until recently the only small piroplasm known to parasitise dogs. Haematological and serum biochemistry analyses showed that almost all the dogs had an intense regenerative haemolytic anaemia and that in some cases there was evidence of renal failure. A molecular study was made of a sample of the parasite obtained in June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
70
1
7

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 5 publications
0
70
1
7
Order By: Relevance
“…B. annae infection has been associated with a severe haemolytic anaemia [3]. The resulting haemoglobinuria could produce a tubulopathy, which will compromise the ability to concentrate urine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B. annae infection has been associated with a severe haemolytic anaemia [3]. The resulting haemoglobinuria could produce a tubulopathy, which will compromise the ability to concentrate urine.…”
Section: Discussionmentioning
confidence: 99%
“…On our first report of a series of cases [3], which followed the first case report of the infection by Zahler et al [23], we obtained mean serum values of total protein and albumin which were within commonly accepted normal reference ranges but we did not study the electrophoretic profile associated to the infection. Furthermore, no reference group of noninfected dogs was included for comparison.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In 2006, 18S rDNA sequence of a European rodent isolate "Munich" (GenBank accession number AB071177) disclosed marked differences from the parasites reported in either the U.S. or Japan [11] but showed high similarity to isolates from rodents (M. arvalis and M. oeconomus) and ticks (Ixodes ricinus) captured in Poland [26,32]. Furthermore, novel genotypes distinct from those commonly distributed in feral rodents in the Holarctic region have been detected repeatedly in such carnivores as fox [8], skunk [8] and river otter [5] in the U.S., raccoons in Japan and the U.S. [8,15], and dogs in Spain (Theileria annae or B. annae) [6,42]. 18S rDNA analyses of these B. microti-group parasites have suggested a monophyletic nature of the B. microti "species" complex, leading to an increasingly large complex under the name B. microti [8,41].…”
mentioning
confidence: 97%
“…The recent knowledge based on genetic analyses of genes from canine piroplasms has shown that there are at least three distinct subtypes or subspecies for small piroplasms: a classic Asian type B. gibsoni; a small organism has been identified recently in northern Spain, which has been given the name Theileria annae; a small organism has been identified in California and remains unnamed [3,15,16,20,21]. Since the P50 gene is cloned from an Asian type B. gibsoni, an experiment is needed to evaluate whether the ELISA with GST-P50t can be used for detecting antibodies to T. annae or unnamed California type small piroplasm in dogs in Europe or North America.…”
Section: Discussionmentioning
confidence: 99%